Hooky - Vol 1 - Tur, Miriam Bonastre (Boston : Etch/Houghton Mifflin Harcourt, 2021)
When Dani and Dorian missed the bus to magic school, they never thought they'd wind up declared traitors to their own kind. Now, thanks to a series of mishaps, they are being chased by powerful magic families seeking the prophesied King of Witches and royals searching for missing princes. But they aren't alone. With a local troublemaker, a princess, and a teacher who can see the future on their side, they might just be able to clear their names--but can they heal their torn kingdom?
Keywords: Twins -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Princesses -- Comic books, strips, etc; Princes -- Comic books, strips, etc; Twins -- Fiction; Magic -- Fiction; Princesses -- Fiction; Princes -- Fiction; Cartoons and comics; Graphic novels